Components Design of a Single Seat Educational Race Vehicle - Fudhail Abdul Munir, F.A. Munir; Mohd Adrinata, Shaharuzaman; Muhammad Zahir , Hassan; Mohd Rody , Mohamad Zin; Mohd Irwan, Mohd Azmi; Nur Rashid , Mat Nuri (2011)
In this research, the methods of developing vital components for the use of single seat educational race vehicle were demonstrated. The vehicle was fitted with a 125 cc four stroke engine located at the rear end. The type of the drive train selected was rear wheel drive. The race vehicle was also equipped with suspension, braking and steering system which similar to conventional passenger car. Before the fabrication of the vehicle took place, thorough engineering analysis was conducted on the designed components. In this stage, the main chassis frame and the brake disc was analyzed using Computer Aided Engineering (CAE) software. The purpose of the analysis was to simulate the strength of the designed components. The analysis was then extended to other vital parts of the vehicle like steering rack, brake disc, engine mounting and knuckles. Modification will be done if the parts fail the simulation test. Next, the fabrications of the parts were done by using facilities available in the faculty. Total duration time of fabrication and assembly of the vehicle parts was approximately two months. Performance analysis was conducted to ensure that each parts of the race vehicle were fully operational. Results show that the race vehicle is fully functional and performed as expected.